Age discrimination and depression among older adults in South Korea: Moderating effects of exercise - Hyun Kang; Emily S. Ihara (Aging and Health Research)
Background: This study examines the association between perceived age discrimination and depression among South Korean older adults and whether regular exercise can moderate this association. There has been a noticeable rise in ageism in both the media and the society during and following the COVID-19 pandemic. Perceived age discrimination can lead to an internalization of ageist attitudes and stereotypes, resulting in decreased self-efficacy and increased negative emotions, which negatively impact on the health of older adults. While regular exercise has been shown to boost self-esteem and enhance positive self-perceptions of aging, its potential as an intervention against the psychological impact of age discrimination is under-explored. Methods: Using data from 9,920 participants (aged 65+) in the 2020 National Survey of Older Koreans, depression was regressed on age discrimination controlling for age, gender, education, marital status, self-rated health, employment status, and activities of daily living (ADLs). A hierarchical multiple regression analysis was employed to examine the moderating effect of exercise. Results: Higher levels of perceived age discrimination were directly associated with higher levels of depression. Regular exercise significantly moderated this relationship, reducing the negative impact of perceived age discrimination on depressive symptoms. Conclusions: Considering the rise of ageism in South Korea, regular exercise can serve as an important mechanism for combating ageism by effectively managing stress and enhancing self-resilience. Our findings highlight the importance of promoting exercise as a potential strategy to mitigate the detrimental mental health effects of age discrimination, particularly in the post-pandemic era.